Mag(u)istradas: a luta pela inserção de mulheres no Tribunal de Justiça de Pernambuco (1978-1983). - Silva, Vanda Lúcia Vieira da (2020)
The work of this report was to discuss elements of “feminization” at the Pernambuco Court of Justice (TJPE), and consequently to give subsidies to the making of a product as an integral part of a Course Conclusion Work. We opted for the elaboration of an illustrated booklet, intended for consultations for attendees at the TJPE Memorial of Justice. To this end, we briefly and contextually report the arrival of Magui Lins Azevedo - the first woman to take office as a magistrate - and we continue with the analysis of the events involving the struggle for the insertion of women in the Pernambuco judiciary. The choice of the time frame, between 1978 and 1983, is justified, since in that period there was a “female occupation”, that is, the effectiveness of judges in the TJPE. The research was developed from a historiographical point of view, therefore, we used the theory of history and other academic texts and in parallel the analysis of newspapers, lawsuits, reports and speeches by parliamentarians. We emphasize that the booklet contains, paths and mishaps about women's struggle, such as the refusal of 91 women to enter a public contest held by the TJPE, at the end of the 1970s, contributing to reflect on the issue of gender inequality in the judiciary.